Peningkatan Literasi Kebencanaan Guna Membangun Kesiapsiagaan Masyarakat Menghadapi Bencana Banjir di Kelurahan Bidara Cina - Rahmat, Hayatul Khairul; Meidiyustiani, Rinny (PT Hakhara Akademia Indonesia, 2024)
Flooding is the overflowing of a river due to water exceeding the capacity of the river so that it overflows and inundates the plains or lower areas around it. DKI Jakarta Province has various complex disaster-related problems with 40% of its area being lowlands that are prone to flooding. One of these areas is Bidara Cina Village which is an area that is often affected by flooding in DKI Jakarta which is located in Jatinegara District, East Jakarta. It should be realized that efforts are needed to reduce the impact of a greater disaster by carrying out holistic and comprehensive disaster management efforts so that the risk of the disaster can be reduced so that it can build community preparedness in an area, especially in RT. 007/ RW. 001 Bidara Cina Village. Based on the above, it is important to carry out community service activities entitled